The synthesis and the cationic fluorescence role of glycols with aromatic end groups, part III - Tuncer, H; Erk, C (Springer, 2003)
Some novel bis-(substituted-phenoxy) ended glycols were synthesised using hydroxy aromatics of vanillin, o-vanillin, iso-vanillin and 4-hydroxy coumarin which reacted with bis-dihalides of polyglycols in the presence of DMSO/alkali carbonate. The novel podands, Ar-(CH2CH2O)(m)-Ar, (m = 1-4), were identified with IR, H-1-NMR, C-13-NMR and mass spectrometry. The various (formyl-methoxy) phenyl and 4-oxycoumarin derivatives of glycols were studied to estimate the cation binding selectivity of SCN- salts of Li+, Na+, K+ and Zn2+ cations in acetonitrile using steady state fluorescence spectroscopy. The relevant structures of podands have shown good selectivity depending on the cation and the glycol length, although the chromophore end groups have no specific contribution on binding.
Keywords: polyethylene glycols; aromatic fluorophores; ion complexing; Li+; Na+; K+; Zn2+